Toxicity characteristics of sewage treatment effluents and potential contribution of micropollutant residuals. Issue 1 (December 2017) - Kim, Younghee; Farnazo, Danvir
Abstract Background A typical sewage treatment plant is designed for organic and nutrient removal from municipal sewage water and not targeted to eliminate micropollutants such as pesticides, pharmaceuticals, and nano-sized metals which become a big concern for sustainable human and ecological system and are mainly discharged from sewage treatment plant. Therefore, despite contaminant removal by wastewater treatment processes, there are still remaining environmental risks by untreated pollutants in STP (sewage treatment plant) effluents. This study performed aquatic toxicity tests of raw wastewater and treated effluents in two sewage treatment plants to evaluate toxicity reduction by wastewater treatment process and analyze concentration of contaminants to reveal potential toxic factors in STP effluents. Methods Water samples were collected from each treatment steps of two STPs, and acute and chronic toxicity tests were conducted following USEPA (United States Environmental Protection Agency) and OECD (Organization for Economic Cooperation and Development) guidelines. Endpoints were immobility for mortality and reproduction effect for estrogenicity. Results Acute EC50 s (median effective concentration) of influents for Seungki (SK) and Jungnang (JN) STPs are 54.13 ± 32.64% and 30.38 ± 24.96%, respectively, and reduced to 96.49 ± 7.84% and 100%. Acute toxicity reduction was clearly correlated with SS (suspended solids) concentration because of filter feeding characteristics of test organisms. Chronic toxicity tests revealed that lethal effect was reduced and low concentration of influents showed higher number of neonates. However, toxicity reduction was not related to nutrient removal. Fecundity effect positively increased in treated wastewater compared to that in raw wastewater, and no significant differences were observed compared to the control group in JN final effluent implying potential effects of estrogenic compounds in the STP effluents. Conclusions Conventional wastewater treatment process reduced some organics and nutritional compounds from wastewater, and it results in toxicity reduction in lethal effect and positive reproductive effect but not showing correlation. Unknown estrogenic compounds could be a reason causing the increase of brood size. This study suggests that pharmaceutical residues and nanoparticles in STP effluents are one of the major micropollutants and underline as one of estrogenic effect factors.